2004
DOI: 10.1016/j.jpcs.2003.08.032
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of [Pt(NH3)4]2+ ions into layered sodium silicate magadiite: a useful method to enhance their stabilisation in a highly dispersed state

Abstract: Al-free layered sodium silicate magadiite has been used as the host material for the stabilisation of [Pt(NH3)4] 2+ ions via intercalation and/or ionexchange reactions. The stabilisation of Pt(NH3)4] 2+ ions in between the layers of Na-magadiite was confirmed by thermogravimetric analysis (TGA), where increased decomposition temperatures were observed for the intercalated materials. The intercalation behaviour of Na-magadiite was evident from the significant uptake of Pt ions (22.2 wt.%). When silica gel was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…However, until now, only a limited number of studies have been reported on such nanocomposite materials. 6,9 Recently, we successfully prepared Ag-magadiite nanocomposites based on two types of magadiite materials: Na-magadiite and H-magadiite. For these nanocomposites, it was found that Ag-nanoparticles consisting of a single-crystalline particle with 0955-2219/$ -see front matter © 2006 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, only a limited number of studies have been reported on such nanocomposite materials. 6,9 Recently, we successfully prepared Ag-magadiite nanocomposites based on two types of magadiite materials: Na-magadiite and H-magadiite. For these nanocomposites, it was found that Ag-nanoparticles consisting of a single-crystalline particle with 0955-2219/$ -see front matter © 2006 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…Magadiite (Na 2 Si 14 O 29 ·nH 2 O) is a layered silicate consisting of negatively charged silicate layers and Na + cations in the interlayer nanospace, and has characteristics such as easy availability by a simple hydrothermal procedure [ 33 ] and high cation-exchange capacity (180 meq/100 g) [ 34 ]. The accessibility and cation-exchange ability of magadiite have led to several applications, for example, adsorbents of metal species [ 35 ] and building units of photofunctional materials [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…SNCM was synthesized using hydrothermal treatment under autogenous pressure at 150 °C of a viscous weak alkaline and SiO 2 -rich area of the ternary system Na 2 O/SiO 2 /H 2 O [ 35 ]. The molar gel composition was 5 SiO 2 :Na 2 O:75 H 2 O.…”
Section: Methodsmentioning
confidence: 99%